The influence of geometrically nonlinear effects on the progressive collapse of reinforced concrete structures. - Oliveira, Cláudio Ernani Martins (2015)
Programa de Pós Graduação em Engenharia Civil. Departamento de Engenharia Civil, Escola de Minas, Universidade Federal de Ouro Preto.